Sinking Rate and Community Structures of Autumn Phytoplankton Responses to Mesoscale Physical Processes in the Western South China Sea - Mao, Yingjie; Li, Xiaoqian; Zhang, Guicheng; Liao, Yan; Qian, Gang; Sun, Jun (Frontiers in Microbiology, 2021)
To examine the influence of mesoscale eddy on the natural phytoplankton community and its sinking rate changes, a comprehensive investigation cruise was carried out in the western South China Sea (wSCS) in autumn 2016. A total of 108 phytoplankton species were found which belong to 54 phytoplankton genera, most of them was dominated by Dinophyta (54 genera), then in turn followed by Bacillariophyta (50 genera), Cyanophyta (3 genera) and Chrysophyta (1 genus). Bacillariophyta and Dinophyta were the main phytoplankton communities in the investigated sea area. The sinking rate of phytoplankton ranged from 0.12 to 3.17 m d-1, determined with the SETCOL method. The highest phytoplankton sinking rate was found in the 200 m water layer, followed by the DCM layer. No significant correlation was found between phytoplankton sinking rates and most of the environmental parameters during this cruise. At the similar time, we have carried out the estimation of carbon fluxe in the investigated sea area by using the singking rate of phytoplankton, which showed that the carbon flux ranged from 2.41×10-6 to 0.006 mg C m-2 d-1, in addition, the maximum was in 200 m layer. Phytoplankton community and sinking rate was significantly affected by the mesoscale eddy processes. The cold eddy could affect the community distribution of Bacillariophyta and Dinophyta, and the upwelling mainly affects the community of Dinophyta. Both of them could contribute to a higher sedimentation rate of phytoplankton in the surface and DCM layers. Warm eddy could reduce the abundance of phytoplankton in the surface layer, simultaneously the sinking rate of phytoplankton in the shallow water layer above 100 m also gets reduced. These results can fill in the knowledge gap of mesoscale eddy processes in the study of phytoplankton community change and sinking rate, furthermore it can provide insights thoughts of phytoplankton carbon and its implementation in further carbon sink.